Challenges in the diagnosis and management of vitreoretinal lymphoma – Clinical and basic approaches. (September 2022) - Takase, Hiroshi; Arai, Ayako; Iwasaki, Yuko; Imai, Ayano; Nagao, Toshikage; Kawagishi, Masahiko; Ishida, Tomoka; Mochizuki, Manabu
Abstract: Vitreoretinal lymphoma (VRL) is a subtype of diffuse large B-cell lymphoma and is sight- and life-threatening in the vast majority of patients. Lymphoma cells infiltrate the vitreous body and/or subretinal space and exhibit clinical signs of vitreous opacities and creamy white subretinal lesions. Although the intraocular signs can serve as clues to suspect VRL, they are nonspecific and may be misdiagnosed as uveitis. Histopathological evidence of malignant cells on vitreous biopsy, for instance, is the gold standard for diagnosis of VRL; however, cytological examination of the vitreous often results in a low success rate owing to the small quantity and poor quality of tissues and cells in the sample. Recent advancements in immunological, molecular, and gene analyses using intraocular samples have made it possible to accurately diagnose VRL. As for the management of VRL, local treatments with irradiation and/or intravitreal injections of anti-tumor agents (methotrexate or rituximab) are effective in suppressing intraocular VRL lesions. However, the effect of systemic chemotherapy, with or without brain irradiation, on preventing central nervous system involvements remains controversial. In this review article, we discuss the following concepts based on previous literature and our unpublished results: current ocular imaging examinations such as optical coherence tomography and fundus autofluorescence; immunological, molecular, and gene expression characterization of intraocular biopsies with special attention to flow cytometry; immunoglobulin gene rearrangement assays that use the polymerase chain reaction test; cytokine assays; gene mutations ( MYD88, CD79B ); and current local and systemic treatments of VRL. Highlights: Vitreoretinal lymphoma (VRL) is a subtype of diffuse large B-cell lymphoma. Its global incidence is rising, and its diagnosis and treatment remain difficult. We review methods for the diagnosis and treatment of VRL and future perspectives. We synthesize clinical findings of our research group and those of other studies.